On the local Hurst exponent of geomagnetic field fluctuations: Spatial distribution for different geomagnetic activity levels. Issue 4 (17th April 2015) - Michelis, Paola De; Consolini, Giuseppe
Abstract This study attempts to characterize the spatial distribution of the scaling features of the short time scale magnetic field fluctuations obtained from 45 ground‐based geomagnetic observatories distributed in the Northern Hemisphere. We investigate the changes of the scaling properties of the geomagnetic field fluctuations by evaluating the local Hurst exponent and reconstruct maps of this index as a function of the geomagnetic activity level. These maps permit us to localize the different latitudinal structures responsible for disturbances and related to the ionospheric current systems. We find that the geomagnetic field fluctuations associated with the different ionospheric current systems have different scaling features, which can be evidenced by the local Hurst exponent. We also find that in general, the local Hurst exponent for quiet magnetospheric periods is higher than that for more active periods suggesting that the dynamical processes that are activated during disturbed times are responsible for changes in the nature of the geomagnetic field fluctuations.